2015
DOI: 10.1007/s10973-015-4782-y
|View full text |Cite
|
Sign up to set email alerts
|

Heat of hydration of low-clinker cements

Abstract: The hydration heat evolution of low clinker cements is studied in a dependence on the testing method and temperature. Four substitution rates of ordinary Portland cement by ground granulated blast furnace slag or siliceous fly ash were used-10, 30, 50 and 70 %. In all cases, the water/binder ratio of the cement paste was 0.5. The heat evolution and the heat evolution rate were monitored over 72 h with the use of two testing methods. The isothermal measurements were carried out with the use of TAM Air isotherma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(22 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…There is great interest in composites containing high amount (50% and higher) of cement replacements. For example, attempts of incorporating various additives in cement pastes, such as siliceous fly ash, metakaolin or slag, were presented in works [1][2][3]. The additives have a significant impact on lowering the heat of hydration and the rate of heat evolution of composite binders.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is great interest in composites containing high amount (50% and higher) of cement replacements. For example, attempts of incorporating various additives in cement pastes, such as siliceous fly ash, metakaolin or slag, were presented in works [1][2][3]. The additives have a significant impact on lowering the heat of hydration and the rate of heat evolution of composite binders.…”
Section: Introductionmentioning
confidence: 99%
“…In case of low-calcium fly ash, lengthening of induction period and reduction of intensity of acceleration period are observed. The more of such component is added, the stronger the effects are observed [1,2,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lawrence, et al have shown that limestone in cement increases early age mechanical strength because of its reactions with the C 3 A and C 4 AF phases (formation of aluminates and carboaluminates) but later its impact becomes marginal [37,38]. As a result of their low early age reactivity [29,30,39] and 6 the increase in the length of the dormant period [40,41], slag and fly ash produce low hydration heat with time. The compressive strength is lower at early age but similar to or higher than compressive strength after 28 days for concretes without slag and fly ash considering an equal binder content [30,42].…”
Section: Current State Of Knowledgementioning
confidence: 99%
“…Modelling of transport processes and hydration phenomena in early age concrete is a challenging engineering problem, since hydration of cement is an exothermic reaction, which may result in high temperatures and related deformations, stresses, and cracking in concrete structures, e.g. [1][2][3][4][5][6][7] and references therein.…”
Section: Introductionmentioning
confidence: 99%